CONFLICT RESOLUTION AND SUCCESSION PLANNING IN THE FAMILY BUSINESS PT. SOKA ABADI - Danaparamita, Faisal Akbar; Sutanto, J.E. (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This study aims to explore conflict resolution and succession planning in the family business PT. Soka Abadi, a family-owned company in the property sector specializing in residential developments and commercial complexes. The main issues faced by PT. Soka Abadi include family conflicts that negatively impact the company and the preparation of potential successors to lead the family business. Utilizing a qualitative research method, the study employs semi-structured interviews for data collection. To ensure the validity and reliability of the findings, the author applies source triangulation. The collected data is then reduced and analyzed to inform conflict resolution and succession planning. The results indicate several strategies for resolving conflicts in family businesses, including pruning the family tree, revolving office roles, participative decision-making, and organizational restructuring. Furthermore, the findings reveal that the succession preparation process at PT. Soka Abadi is effectively progressing through the implementation of necessary functions. Overall, the study highlights the importance of addressing family conflicts and establishing a clear succession plan to ensure the longevity and success of the family business.